Novel adsorptive membrane through embedding thiol-functionalized hydrous manganese oxide into PVC electrospun nanofiber for dynamic removal of Cu(II) and Ni(II) ions from aqueous solution. (October 2020) - Hezarjaribi, M.; Bakeri, Gh.; Sillanpää, M.; Chaichi, M.J.; Akbari, S.
Graphical abstract: Highlights: Adsorptive PVC ENMs were fabricated in an efficient way to remove Cu(II) and Ni(II). HMO/Sil NPs were incorporated into PVC ENMs matrices with improved dispersibility. The fabricated ENMs showed high flux and superior metal ion removal efficiency. The ENMs were regenerated without any significant performance loss and reused well. Abstract: An efficient material and method is always welcoming for the water treatment technologies. The objective of this research was to fabricate and evaluate the adsorptive electrospun nanofiber membranes (ENMs) for the dynamic removal of copper and nickel ions via ultrafiltration process. As-synthesized hydrous manganese oxide (HMO) nanoparticles was functionalized with mercaptosilane coupling agent and then directly embedded into polyvinyl chloride nanofiber matrices through electrospinning process. The prepared nanoparticles and ENMs was systematically characterized and then, the ultrafiltration experiments for Cu(II) and Ni(II) ions removal were performed in continuous filtration mode. The effective experimental parameters including initial metal ion concentrations, contact time, nanoparticles dosage, feed temperature and the interfering ion (Zn 2+ ) on the Cu(II) and Ni(II) removal efficiency were investigated. The results showed that the fabricated ENMs with 1.5 wt% of nanoadsorbents exhibited excellent capability for the removal of both metal ions compared to the membranes with 0.5 and 1 wt% loading. The Cu(II) removal efficiency by the membranes containing 1.5 wt% of modified and virgin HMO was 89.26 % and 79.20 %, respectively which was higher than Ni(II) removal efficiency. The results demonstrated that the maximum Cu(II) and Ni(II) removal efficiency (∼90 % and 80 %, respectively) was achieved by membranes which containing modified adsorbents because of the strong chelating power and high affinity of reactive thiol groups on the adsorbents. Furthermore, the presence of interfering ion didn't make any change on the metal ions removal. The prepared ENMs showed excellent performance in the removal of metal ions even after four sorption-desorption continuous cycles.